Highly cited papers in Slovenia - Pečlin, Stojan (Teorija in praksa, 2014)
Despite some criticism and the search for alternative methods of citation analysis it's an important bibliometric method, which measures the impact of published research results. In the last decade, special attention has been paid to highly cited papers, publications representing the highest quality, scientific excellence. In two studies, we have studied the highly cited papers in Slovenian co-authorship published in journals indexed in the bibliographic databases Web of Science and Scopus. These are defined as papers ranking by the number of citations among the top per cent in a given research field. The first hypothesis was that highly cited publications co-authored by Slovenian researchers are published in the top quarter ranked journals in a given field of research, and the second that these papers are written in international collaboration and that Slovenian authors are a minority among the authors. The hypothesis that Slovenian authors form a minority in international co-authored teams was confirmed only in the case of the top one per cent most cited publications, but not in the case of publications in the top ten per cent most cited publications. The use of indicators related to most prestigious journals for the evaluation purposes is particularly well suited when growth in the number of publications is high, but the impact is not corresponding, as is the case in Slovenia.
Keywords: Articles; Bibliometrics; bibliometrične analize; Bibliometrija; Citation; Citiranje; Članki; Slovenia; Slovenija